The Relationship Between Work Life Balance and Burnout in Health Workers in a Public Health Center. - Azizoglu, Fatma; Yel, Pinar; Terzi, Banu; Mentese, Emine; Kutlu, Leman (International Journal of Caring Sciences)
Background: This study examined the relationship between work-life balance and burnout levels in primary healthcare workers in Istanbul during the pandemic. Method: The descriptive and cross-sectional study population consisted of 216 primary healthcare workers (N=216). Among multidisciplinary healthcare professionals; doctors 36.5%, nurses 23%, emergency medical technicians 6.3%, medical officers 4%, midwives 15.1%, and others 15.1%. Data were collected using the "Information Form", "Work-Life Balance Scale", and "Maslach Burnout Scale". Mann-Whitney U test, Kruskal-Wallis test, and Dunn-Bonferroni test were used for data analysis. Spearman's correlation analysis was used to evaluate the relationships between quantitative variables. Results: The sub-dimensions of the participants' work-life balance, work-life adjustment, neglecting life, taking time for oneself, and life consists of work; the overall total score averages were 2.89±0.83, 2.89±0.67, 2.99±0,87, 3.41±0.92 and 3.04±0.62, respectively. The participants' burnout emotional sub-dimension mean score was 29.86±8.56, the mean score was 11.65±4.74, personal achievement sub-dimension mean score was 17.79±5.82, and the overall burnout score average was 59.30±14.44. There was a statistically significant negative moderate correlation between the Maslach Burnout Scale total score average and the Work-Life Balance Scale total score mean of the participants (r=-0.588; p=0.001; p<0.01). Conclusion: Emotional exhaustion and depersonalization are the most important factors that disrupt work-life balance. The factors that cause emotional exhaustion and depersonalization among family health workers should be determined. Interventions should be planned to ensure work-life balance by eliminating these factors.